Biophysical investigations of the mechanism of colicin translocation - Hands, Sarah Louise (2005)
Colicins are a family of bacterial toxins, which kill Escherichia coli cells and other closely related species. Their mode of action requires binding to an outer membrane receptor, translocation across the outer membrane and periplasm and cytotoxic action on a specific target. Colicins usually kill cells either by attacking the bacterial RNA or DNA or by forming pores in the inner membrane of the cell. Their cytotoxic activity can be inhibited by the high affinity binding of an immunity protein.